DICTING AS A METHOD OF DIFFERENTIATED LEARNING FOR STUDENTS WITH A NON-RUSSIAN LANGUAGE OF TEACHING - M. M. Komilova (Journals Park Publishing, 2023)
The article deals with the issue of the development of written speech of students of secondary and secondary specialized education in Uzbekistan. The causes of the problem are analyzed. Various types of dictation are offered as a way to develop students' literate speech on the example of the Russian language. A differentiated approach is recommended to teaching the Russian language as a solution to the problem of written illiteracy.
Keywords: differentiated approach, level approach, written speech, Russian language, educational and creative types of dictation: vocabulary, visual, pictorial and graphic.